Determination of human reference values for serum total 1, 25-dihydroxyvitamin D using an extensively validated 2D ID-UPLC–MS/MS method. Issue 164 (November 2016) - Dirks, Niek F.; Martens, Frans; Vanderschueren, Dirk; Billen, Jaak; Pauwels, Steven; Ackermans, Mariëtte T.; Endert, Erik; Heijer, Martin den; Blankenstein, Marinus A.; Heijboer, Annemieke C.
Highlights: We have developed a LC–MS/MS method able to measure both 1, 25dihydroxyvitamin D3 and D2 . The method was extensively validated with regard to sensitivity, specificity and robustness and correlated well with another published LC–MS/MS method. Human reference values for 1, 25-dihydroxyvitamin D3 and D2 were 59–159 pmol/L and <17 pmol/L, respectively. Premenopausal women taking oral contraceptive pills show significantly higher 1, 25-dihydroxyvitamin D3 values compared to postmenopausal women. Abstract: Background: To assess a patient's vitamin D status the precursor metabolite 25-hydroxyvitamin D can be determined. However, measurement of 1, 25-dihydroxyvitamin D is required when disorders of 1a-hydroxylation, extrarenal 1a-hydroxylation, or vitamin D receptor defects are suspected. Methods: The aim of this study was to determine reference values for 1, 25-dihydroxyvitamin D3 and D2 using a 2D ID-UPLC–MS/MS method. Results: The LC–MS/MS method, able to measure picomolar concentrations of both 1, 25-dihydroxyvitamin D3 and D2 in human serum, was extensively validated. Intra-assay variations were <5% and 8.5% and <7.5% and 11%, for 1, 25-dihydroxyvitamin D3 and D2, respectively, over the whole dynamic range (3.1–376 and 3.1–652 pmol/L). Limit of quantitation was 3.4 pmol/L for both compounds. Our method correlated well with a published LC–MS/MS method ( r  = 0.87) and with the average 1, 25-dihydroxyvitamin D3 results of the vitamin D External Quality Assessment Scheme (DEQAS) determined with LC–MS/MS ( r  = 0.93). Reference ranges, determined in 96 plasma samples of healthy volunteers were 59–159 pmol/L and <17 pmol/L for respectively 1, 25-dihydroxyvitamin D3 and D2 . The female part of the reference group showed a statistically significant decrease of 1, 25-dihydroxyvitamin D3 concentrations with age. The presence of significantly higher average 1, 25-dihydroxyvitamin D3 levels in premenopausal women taking oral contraceptive pills compared to postmenopausal women suggests that this effect is estrogen-related, as estrogens lead to a higher vitamin D binding protein. Conclusions: The major finding of the present study is a reference interval of 59–159 pmol/L for 1, 25-dihydroxyvitamin D3 determined with a highly sensitive and precise LC–MS/MS method.